A Review of the Effects of Major Atmospheric Pollutants on Pollen Grains, Pollen Content, and Allergenicity. (24th December 2015) - Sénéchal, Hélène; Visez, Nicolas; Charpin, Denis; Shahali, Youcef; Peltre, Gabriel; Biolley, Jean-Philippe; Lhuissier, Franck; Couderc, Rémy; Yamada, Ohri; Malrat-Domenge, Audrey; Pham-Thi, Nhân; Poncet, Pascal; et al.
Abstract : This review summarizes the available data related to the effects of air pollution on pollen grains from different plant species. Several studies carried out either on in situ harvested pollen or on pollen exposed in different places more or less polluted are presented and discussed. The different experimental procedures used to monitor the impact of pollution on pollen grains and on various produced external or internal subparticles are listed. Physicochemical and biological effects of artificial pollution (gaseous and particulate) on pollen from different plants, in different laboratory conditions, are considered. The effects of polluted pollen grains, subparticles, and derived aeroallergens in animal models, in in vitro cell culture, on healthy human and allergic patients are described. Combined effects of atmospheric pollutants and pollen grains-derived biological material on allergic population are specifically discussed. Within the notion of " polluen, " some methodological biases are underlined and research tracks in this field are proposed.